Socialization of the Importance of Building English Skills for Elementary School Children at SD Negeri 122395 Pematang Siantar - Herman Herman; Vera Elisabet Siahaan; Angel Nerin Patricia Panggabean; Hanji Agustina Sitohang; Theresi Theresi; Santa Veronika Situmorang; Fitrianti Manurung; Yanti Kristina Sinaga; Irene Adryani Nababan; Prakash Puhka (Pengabdian: Jurnal Abdimas, 2023)
Background. The results of observing the abilities of students at this school, it can be seen that grade 5 students at SD Negeri 122395 Pematangsiantar have the basic skills to master the use of English well. Purpose. This study aimed to investigate the importance of giving socialization to the students about basic skills that the students need to acquire in learning English well. Method. This ability can be seen from the speed of students in understanding and responding to learning that has been socialized. Grade 5 students of SD Negeri 122395 Pematangsiantar consisting of 20 students are the subject of this observation. This socialization was conducted at SD Negeri 122395 Pematang Siantar. Three phases were implemented such as preparation, implementation and evaluation. Results. The results showed that importance of building English skills starts from elementary school. Interesting learning methods can also build student activity and skills in the learning process that takes place in the classroom. Conclusion. This is also based on the communication skills that students get in the learning process, not only limited to knowledge, students will be motivated and feel that what they have learned will be useful and used in the future..